EFEKTIVITAS SISTEM INFORMASI AKUNTANSI PENJUALAN (Studi Kasus: UMKM Penggilingan Biji Plastik Masrur Tangerang) - Ekawanti, Wahyumi (Yayasan Nuraini Ibrahim Mandiri, 2024)
Accounting information systems manage various transaction data, both financial and non- financial, which influence the processing of financial transactions. Effectiveness is a benchmark that describes the extent to which goals are to be achieved. The purpose of this research is to determine the effectiveness of implementing an accounting information system implemented by the Masrur Tangerang Plastic Seed Milling UMKM. This is a qualitative research, and researchers collect data through observation, interviews, and documentation. The results of this research indicate that the sales accounting information system at the Masrur Iron Ore Milling UMKM has been running well and implemented very simply. This is because the system is implemented manually where document archiving is still not optimal and sales invoice documents have not been archived and are still being recorded in MS. Excel. Additionally, effectiveness The accounting information system, seen from an internal control perspective, has not been able to meet the owner's immediate needs. This can be seen from the research findings, which shows that the system used should involve technology by adding hardware components and software components and can also add network components such as WiFi or hotspots so that the resulting accounting information is free from the risk of errors and data backup can be carried out optimally.